Perlindungan Hukum Pemenang Lelang Eksekusi Hak Tanggungan Pada Kantor Pelayanan Kekayaan Negara dan Lelang (KPKNL) Pekanbaru - Yenti Murni; Suharizal Suharizal; Beatrix Benni (Simbur Cahaya, 2018)
The mortgageis legal protection for the creditor if the debtor cannot perform its obligation to pay off the debt to the creditor. Repayment of creditor debt is made by selling the object of guarantee of mortgage rights through public tender. The auction process will result in legal effect, namely the transfer of rights of auction object from the seller to the auction winner. This research is aimed to know the execution auction of mortgage right  State Property Office and Auction (KPKNL) Pekanbaru, the legal consequences for the auction winner who can not control the auction object of mortgage execution, and the legal protection to a winner of the auction of mortgage execution. The research me tho duse disjuridical empirical with an alytical, descriptive research specification. Primary and secondary data were obtained through a literature study and a survey.  Data collection tools are interviews. Data obtained is analyzed quantitatively.  The result of there searchs how sthat the executio nauction of mortgage rightsat KPKNL Pekanbaru is implemented based on the Regulation of Minister of Finance of the Republic of Indonesia Number 27 / PMK.06 / 2016, and is related to Regulation of the Minister of Finance Number 106 / PMK.06 / 2013 regarding the amendment to Regulation of the Minister of Finance Number 93 / PMK.06 / 2010 concerning the instruction of auction implementation. In respect of the legal consequences of the auction winner being unable to control the auction object, the auction winner may apply for the auction of auction object to the head of the local district court. The auction treaty normatively supports the legal protection of the winner of the auction as an authentic deed. However, a legal certainty to control the objec to fanauction is not obtained as the law does not explicitly regulate the protection of the winner of the auction.